1995
DOI: 10.1017/s0022215100131251
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal carcinoma ex-papilloma in a non-irradiated, non-smoking patient: a clinical record and review of the literature

Abstract: Malignant transformation of respiratory papillomata is not uncommon in the presence of precipitating factors such as tobacco smoking and therapeutic irradiation. Respiratory papilloma changing to carcinoma in the absence of smoking and irradiation is seldom seen, with only about 20 documented cases presented in the literature. Here we report one such case in a 30-year-old male patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Malignant transformation in non-irradiated and non-smoking patients suffering from respiratory papillomas is a very rare event. Only 13 patients with recurrent papillomatosis who developed a broncho-pulmonary carcinoma are reported in the literature [18]. However, one of our patients with juvenile multiple RRP and bronchial spreading of papillomatosis developed a bronchiogenic carcinoma without any history of smoking.…”
Section: Classification Clinical Course and Malignancymentioning
confidence: 68%
“…Malignant transformation in non-irradiated and non-smoking patients suffering from respiratory papillomas is a very rare event. Only 13 patients with recurrent papillomatosis who developed a broncho-pulmonary carcinoma are reported in the literature [18]. However, one of our patients with juvenile multiple RRP and bronchial spreading of papillomatosis developed a bronchiogenic carcinoma without any history of smoking.…”
Section: Classification Clinical Course and Malignancymentioning
confidence: 68%
“…All of eight HPV11 isolates from papillomas and laryngeal cancer were identical to the prototype in this region of the URR (data not shown). The involvement of other agents in both HPV-related and unrelated carcinogeneses is well documented, with radiotherapy and smoking the prime candidates in RRP (15). It is noteworthy that patient 27 had been a heavy smoker from the age of 10 years until his death at age 25 years and had received treatment with several chemotherapeutic agents (e.g., interferon, adenine arabinoside, and cimetidine) which are recognized as potential cofactors in the malignant progression of RRP lesions (13).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of high-grade dysplasia for LP is between 10% and 17.6% [2426]. The progression of LP with dysplasia with multiple recurrences to carcinoma was reported [10]. Hall et al [27] reported that only one (2%) of the 54 adult patients with recurrent respiratory papillomatosis developed SCC.…”
Section: Discussionmentioning
confidence: 99%